Vapor Chamber Embedded With Hollow Condenser Tubes Heat Sink. - Goh, Wen Qian (2017)

(untitled)
A novel vapor chamber with embedded hollow condenser tubes heat sink was designed and fabricated. Experiments were carried out to determine its thermal performance. The device was used to improve the thermal management of electronic packages. In this study, two vapor chambers heat sinks were tested using different fill ratios. Natural and forced convection as cooling model were employed and subjected to two different power inputs of 10W and 20W. The results of this investigation showed that, Force Convection performs better with lower thermal resistance compared to Natural Convection, Under Natural Convection, lower Fill Ratio (FR=0.5) performs better, Under Forced Convection, higher Fill Ratio (FR=1.0) performs better, Under Natural Convection, lower Fill Ratio does not affect the performance of Vapor Chamber #1 & Vapor Chamber #2 and Under Forced Convection and at low Fill Ratio, Vapor Chamber #2 performs better than Vapor Chamber #1.